AKUMULASISOLUT DAN REGULASIOSMOTIK DALAM SEL TUMBUHAN PADA KONDISISTRES AIR - B Paul Naiola (BERITA BIOLOGI, 2005)
One of the interesting topic in Plant-Water Relations is the synthesis and accumulation of solutes by plant cells and within thosecells. This paper is to make a short review upon this topic. It shows the relationship of water potential components of plant cells (a - total water potential, 0n - osmotic potential and 0p-turgor pressure), in accordance with environmental fluctuations (especially water stress), osmotic regulation (osmotic adjustment) and the role of solute synthesis and accumulation in plant cells when drought develop. Proline (among sugars and organic acids), dominates most of the available reports as both an osmotic constituent/ osmotic agent and a compatible solute. Such a reviewed topic that still less available in Indonesian.